Entre a cultura africana, o Islão e o legado do processo colonizatório: Uma análise sobre o Protocolo do Maputo e os direitos da mulher na Guiné-Bissau - Té, Mário (2024)
This dissertation deals with African culture, Islam, and the legacy of the colonization process, with the main objective of analyzing the situation of women's human rights in Guinea-Bissau in relation to ethnic traditions and Islamic culture. To this end, the research was conducted using a qualitative approach, developed from critical and decolonial theory, whose adopted technique is textual analysis. Among the diverse debates held regarding cultural particularities among human societies, especially between Euro-Western, Islamic and African societies, the gender debate stands out as a fundamental point in which power is exercised in several dimensions. Through an approach that questions the encounters that emerged at different times in African lands, the research recognizes that the processes of Islamization and colonization produced structures in Africa that were adverse to those that once made harmonious and complementary coexistence between men and women possible. This will later be conditioned by the need to adopt human rights in Africa, especially women's rights, but from a liberal-individualist perspective that is different from the African collectivist perspective. Specifically, we will look at the reality of women and their rights in Guinea Bissau in light of the political structure, Islamic culture and ethnic traditions of Guinea Bissau, knowing that some practices of these structures contribute to the violation of women's rights in this country. To this end, we conclude that it is necessary that the Guinean State, in addition to adopting women's rights standards, must opt for a strategy to combat the sentimental side that motivates traditional and Islamic practices that are detrimental to the human dignity of Guinean women.